2018
DOI: 10.1021/acs.inorgchem.8b02517
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Global Electrophilicity Index (GEI) as a Measure of Lewis Acidity

Abstract: The global electrophilicity index (GEI) has been further explored as a general and base-free metric for Lewis acidity. A number of computational methods, including post-Hartree–Fock, density functional theory, and time-dependent density functional theory, have been explored. In this fashion, we sought the method most applicable to a range of different Lewis acids with differing structural and electronic features, including boron trihalides, silicon tetrahalides, fluoroaryl boranes, and group 15 pentahalides. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 96 publications
5
60
0
2
Order By: Relevance
“…Most of the previous calculated values reported in the literature (See Table S1 of the Supporting Information) are close to 500 kJ mol −1 , and therefore close to our LC‐WPBE estimated value. More importantly this estimate is also very close the most accurate (DLPNO‐CCSD(T)/cc‐aug‐pVQZ) calculation reported in the literature, and other very recent estimates using pseudo‐isodesmic schemes . An excellent and very complete compilation on the FIA of SbF 5 was recently reported by Greb …”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Most of the previous calculated values reported in the literature (See Table S1 of the Supporting Information) are close to 500 kJ mol −1 , and therefore close to our LC‐WPBE estimated value. More importantly this estimate is also very close the most accurate (DLPNO‐CCSD(T)/cc‐aug‐pVQZ) calculation reported in the literature, and other very recent estimates using pseudo‐isodesmic schemes . An excellent and very complete compilation on the FIA of SbF 5 was recently reported by Greb …”
Section: Resultssupporting
confidence: 85%
“…More importantly this estimate is also very close the most accurate (DLPNO-CCSD(T)/cc-aug-pVQZ) calculation reported in the literature, [37] and other very recent estimates using pseudoisodesmic schemes. [46] An excellent and very complete compilation on the FIA of SbF 5 was recently reported by Greb. [47] Furthermore, the value obtained with the LC-WPBE approach for the FIA of BF 3 (346.7 kJ mol À 1 ) is not far from the two experimental values reported in the literature, [48,49] (331 � 8 and 328.5 � 13.7 kJ mol À 1 , respectively), and in reasonable agreement with a very recent theoretical estimate (353.4 kJ mol À 1 ) based on the use of Global Electrophilicity Index (GEI) as a Measure of Lewis Acidity.…”
Section: Sbcl 5 Adductsmentioning
confidence: 95%
“…We note, that these cations are very strong Lewis acids with FIA values of 775 (S); 803 (Se) and 844 (Te) kJ mol À1 that could be relevant in view of the renewed interest 46 in strong 47 (also cationic 48 ) Lewis acids. 49 They should be compared to classical phosphenium ions [PR 2 ] + with FIA values of 721 (R ¼ NMe 2 ), 789 (R ¼ Mes) and 828 (R ¼ Ph). 50 The easily and in high yield accessible salts ECl 3 [WCA] were tested for their reaction with the known P 3 3À precursor Na[Nb(P 3 )(ODipp) 3 ], related to the synthesis of AsP 3 from AsCl 3 .…”
Section: Resultsmentioning
confidence: 99%
“…TheG utmann-Beckett test and global electrophility index DFT investigations were undertaken to assess the relative Lewis acidity of 1 and 2. [49,50] Both studies revealed them to be weak Lewis acids (see Supporting Information). Undeterred by these results,w ef ocused our efforts on reactivity by studying 1 and 2 in five benchmark catalytic reactions ( Figure 3).…”
Section: Nitrenium Salts In Lewis Acid Catalysismentioning
confidence: 99%